2014
DOI: 10.1371/journal.pone.0111624
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas: A Comparative Study of 68Ga-DOTATOC, 68Ga-DOTANOC and 68Ga-DOTATATE for Molecular Imaging in Mice

Abstract: PurposeThe goal of this study was to compare the tumor uptake kinetics and diagnostic value of three 68Ga-DOTA-labeled somatostatin analogues (68Ga-DOTATOC, 68Ga-DOTANOC, and 68Ga-DOTATATE) using PET/CT in a murine model with subcutaneous meningioma xenografts.MethodsThe experiment was performed with 16 male NUDE NU/NU mice bearing xenografts of a human meningioma cell line (CH-157MN). 68Ga-DOTATOC, 68Ga-DOTANOC, and 68Ga-DOTATATE were produced in a FASTLab automated platform. Imaging was performed on an Argus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
(34 reference statements)
2
11
0
1
Order By: Relevance
“…In our tests, the algorithm successfully extracted the TACs for the relevant tissues or regions when the threshold was above a certain critical value, and the results were comparable with those obtained in [37]. Images with lower injected radioactivity, which tend to be more affected by noise, were separated into more clusters for the same threshold value.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In our tests, the algorithm successfully extracted the TACs for the relevant tissues or regions when the threshold was above a certain critical value, and the results were comparable with those obtained in [37]. Images with lower injected radioactivity, which tend to be more affected by noise, were separated into more clusters for the same threshold value.…”
Section: Discussionsupporting
confidence: 67%
“…To do so, we aim to replicate the results obtained in [37] by replacing the manual TAC extraction used in that study with the method presented here. We also include a comparison with the classic k means algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…From a biological standpoint, a recent study confirmed that meningiomas overexpress SST2, with a high expression pattern in 67% of cases, comparable to gastroenteropancreatic NET [5]. These findings agree with imaging studies with 68 Ga-DOTA-SSAs that showed highly elevated tumour uptake [6,7]. 68 Ga-DOTA-SSAs PET/CT is currently recommended in meningioma patients by the international recommendation of the RANO group for differential diagnosis, grading, delineation, radiation planning, follow-up, evaluation of response and progression [1].…”
Section: In Recent Years Peptide Receptor Radionuclide Therapy (Prrtsupporting
confidence: 67%
“…The results presented in this paper, together with the validations presented in [31], demonstrate that the quantitative evaluation of small animal PET images obtained with 68 Ga-DOTA-labeled radiotracers is improved when using appropriate PRC. This improved quantification can increase the diagnostic value of 68 Ga radiotracers, already established or under development [5,[38][39][40]. This would also apply to any preclinical study performed using radiotracers based on medium-large positron range radionuclides, such as O-15, I-124, or Rb-82 [41][42][43][44].…”
Section: Implications Of This Work and Future Researchmentioning
confidence: 91%
“…[ 68 Ga]DOTA-labeled somatostatin analogues bind specifically to somatostatin receptors (SSTRs) and are commonly used for imaging and treatment planning of neuroendocrine tumors (NETs) [3][4][5][6][7][8]. Moreover, [ 68 Ga]DOTA-labeled somatostatin analogues have been reported to show higher sensitivity for the detection of NETs and other somatostatin-receptor expressing tumors than the most widely used radiotracer, 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG), which is used to measure glucose metabolism [9][10][11].…”
Section: Introductionmentioning
confidence: 99%